THE PERCEPTION OF TOUR GUIDE TRAINING: AN INSIGHT FROM THE BORDER AREA OF INDONESIA - Ira Mutiaraningrum; Hikmah Trisnawati; Tita Rosalina (STIE Pariwisata API Yogyakarta, 2021)
Temajuk village is one of the leading tourist attractions in West Kalimantan. It bridges Indonesia and Malaysia. With its rich culture and breathtaking scenery, Temajuk village is indispensably for promoting tourism in West Kalimantan. This study examines the participants’ perception of the tour guide training held in Temajuk Village. The training involved English lessons since the international tourists also visited Temajuk village through Telok Melano, Indonesia. Employing qualitative study, using interview and observation, this study establishes the reasons and expectations underpinning the respondents in joining the training. The responses are presented into the perceived benefits from the participants’ point of view, tour guide training and English language learning, and participants’ expectation. It is advised that this kind of training, especially in the border area can be held to since it is fruitful and prominent.